2019
DOI: 10.1101/585844
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Laminar Specific fMRI Reveals Directed Interactions in Distributed Networks During Language Processing

Abstract: 10Laminar resolution, functional magnetic resonance imaging (lfMRI) is a noninvasive technique with the potential to distinguish top-down and bottom-up signal contributions on the basis of laminar specific interactions between distal regions. Hitherto, lfMRI could not be demonstrated for either whole-brain distributed networks or for complex cognitive tasks. We show that lfMRI can reveal whole-brain directed networks during word reading. We identify distinct, language critical regions based on their 15 associa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 66 publications
(1 reference statement)
1
26
0
Order By: Relevance
“…If the same approach is applied to other regions then the p2t value will need to be adjusted to accommodate different cortical thicknesses using Equation 3. Various studies in laminar fMRI literature (Kok et al, 2016;Lawrence et al, 2019;Lawrence et al, 2018;Sharoh et al, 2019) divide the cortex in three layers, it that case, the equivalent peak to tail ratio to the one observed here would be 2.24.…”
Section: Validation Of the Estimated Psf And Its Approximation As A Psupporting
confidence: 47%
“…If the same approach is applied to other regions then the p2t value will need to be adjusted to accommodate different cortical thicknesses using Equation 3. Various studies in laminar fMRI literature (Kok et al, 2016;Lawrence et al, 2019;Lawrence et al, 2018;Sharoh et al, 2019) divide the cortex in three layers, it that case, the equivalent peak to tail ratio to the one observed here would be 2.24.…”
Section: Validation Of the Estimated Psf And Its Approximation As A Psupporting
confidence: 47%
“…45 Our approach, and that of others, has generally been to identify activated regions on the basis of their aggregate response to the task, either by means of an independent activation study, or by smoothing the high resolution data and using this for a non-laminar analysis. Given that we are interested in the characteristics of the ROI as a whole, 5,18,46 an integration approach, or similar, represents the most logical strategy. Small variations caused by vasculature, or indeed gradients in functionality, will then not be accessible, and would require a different approach.…”
Section: Scope Of This Workmentioning
confidence: 99%
“…Investigating directional laminar connectivity during task conditions has so far remained primarily the domain of invasive electrophysiological investigations in animals (1). In recent years, the development of high-resolution fMRI has made it possible to measure laminar level activity in humans noninvasively (2)(3)(4)(5)(6)(7)(8)(9). Laminar specific anatomical connections directly relate to feedforward and feedback projections between regions at different levels in the cortical hierarchy (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…These projections have been related to frequency-specific directional connectivity derived from electrophysiological measures. Recently, Sharoh et al (9) demonstrated that laminar specific feedforward and feedback connections of the visual word form area with other regions can be studied with cortical depth resolved fMRI. Since frequency-specific electrophysiological synchronization has been directly related to laminar specific feedforward and feedback projections, this raises the question of how frequencyspecific neural synchronization relates to laminar level fMRI connectivity (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation